Quality doubts as a driver for Vocational Education and Training (VET) reforms : Switzerland's way to a highly regarded apprenticeship system - Gonon, Philipp [Verfasser] (My University, 2017)
"Currently, vocational education is being reformed all over the world. On the one hand, this is supposed to provide young people with access to the world of work or at least to make access easier for them, on the other hand vocational education for young adults is also considered an alternative to purely academic education. The latter, it is said, does only prepare for certain professions or is too little specific or not sufficiently relevant for the labour market. Compared to university graduates, young people with workplace training are said to be advantaged when it comes to employability. Furthermore, it is said, vocational education is rather congruent with practical talents and motivations, or vice versa many young people are neither willing nor capable of finding their way through an educational system, which is primarily determined by rewarding performance at school. Another aspect is the clearly higher public expenses connected to rather academic education, and finally one states that there also is question of over-qualification and wrong qualification. These arguments are well known, not new, and they have been stated for years to justify a selective access to the academic career path. However, also access to vocational education is not simply open for everybody, rather one may point out that also vocational educations, in case of workplace training it is the company, which decides about accepting young people for vocational training. " (Author's abstract ; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.1 Westeuropa; S 2.3 Berufsbildungspolitik; L 6 Qualität; Berufsbildungssystem; Schweiz; Bildungsreform; Ausbildungsqualität; Attraktivität